The Effect Of Return On Assets (Roa), Price Earning Ratio (Per), Debt To Equity Ratio (Der), And Dividend Payout Ratio On Price To Book Value (Pbv) Of Shares - Hamidah, Jauharoh Hasna; Hariadi, Bambang (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to examine the effect of Return on Assets (ROA), Price Earning Ratio (PER), Debt to Equity Ratio (DER), and Dividend Payout Ratio on Price to Book Value (PBV). This research was conducted using 15 companies in the Consumer Goods Industry in the Food and Beverages Sub Sector Listed on the Indonesia Stock Exchange, for the period 2015 to 2020. The data was obtained through a purposive sampling technique and multiple linear regression by using the SPSS version 26.0. The data in this study were taken from the company's financial and annual reports, which were obtained from the Indonesia Stock Exchange website or the official website of each company. The results of this study indicate that Return on Assets (ROA) and Price Earning Ratio (PER) have a positive effect on price-to-book value (PBV). In addition, the Debt to Equity Ratio (DER) and the Dividend Payout Ratio also show that they have a positive effect on the Price to Book Value (PBV). Abstrak Penelitian ini bertujuan untuk menguji pengaruh Return on Assets (ROA), Price Earning Ratio (PER), Debt to Equity Ratio (DER), dan Dividend Payout Ratio terhadap Price to Book Value (PBV). Penelitian ini dilakukan dengan menggunakan 15 perusahaan Industri Barang Konsumsi Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia periode tahun 2015 sampai dengan tahun 2020. Data diperoleh melalui teknik purposive sampling dan regresi linier berganda dengan menggunakan SPSS. versi 26.0. Data dalam penelitian ini diambil dari laporan keuangan dan tahunan perusahaan yang diperoleh dari website Bursa Efek Indonesia atau website resmi masing-masing perusahaan. Hasil penelitian ini menunjukkan bahwa Return on Assets (ROA) dan Price Earning Ratio (PER) berpengaruh positif terhadap Price to Book Value (PBV). Selain itu, Debt to Equity Ratio (DER) dan Dividend Payout Ratio juga menunjukkan pengaruh positif terhadap Price to Book Value (PBV).